Gene manipulation applications in autoimmune diseases 1 - Ferreira, Leonardo M. R. (Henry Stewart Talks, 2026)
Autoimmunity, Type 1 diabetes (T1D), T cell-mediated immune tolerance, Regulatory T cells (Tregs), FOXP3 gene, Central and peripheral immune tolerance